TRANSITION OF SENTENCE WORDS: ASPECTS OF MODERN RUSSIAN COMMUNICATIVE DYNAMICS - N. Kovalev (Гуманитарные и юридические исследования)
The article studies speciics of the category of sentence words as a mirror of communicative dynamics. The subject of the study is the transformation in the ield of Russian language communication, ixed in the process of modern use of sentence words in speech activity. In addition, the article discusses the features of transition of S.-W. as units of an inter-level plan based on the works of domestic and foreign linguists. The author's approach to understanding S.-W. is based on the principles of structural-semantic approach, taking into account their communicative-discursive and anthropogenic status. In addition, the principle of dynamic equilibrium between modus and dictum is used in the work as a means of understanding the syncretic links connecting the category S.-W. with other phenomena of the language. Following this principle, the syncretism zones of S.-W. with two-part and one-part sentences, incomplete sentences, phraseological units, facial and non-verbal-graphic means of distance communication were analyzed. Using borrowing from virtual communication as an example, the S.-W. reflect current changes in communication in Russian. The article attempted to comprehend the current trends in communicative dynamics implemented in the sphere of using S-.W. Based on the results of a study covering various groups of speakers in Russian, a number of points were identiied related to the functioning of S.-W. modern Russian language. The study covers not only the sphere of oral speech, but also the area of the so-called virtual communication. The analysis of S.-W. and speech units close to them by certain signs is based on the principle of dynamic equilibrium, which allows a new understanding of syncretic syntactic formations associated with the S.-W. category, among which the following S.-W. are speciied: with a noun in the nominative case as the main component, single-verb sentences with pronounced modality, statements-descriptions of the corresponding human emotion, correlating with non-verbal-graphic elements of virtual communication.